Propuesta metodológica para la renovación de los sistemas y procesos de administración de los mercados eléctricos: el caso colombiano (2015)
The electricity market has been developed in Colombia since 1995, has strengthened institutionally, its development has been dynamic, and also has solved different difficulties. Management systems, that support the market administration, have evolved following this development, however some of these are isolated from each other, or have been developed on different platforms making it difficult to ensure sustainability, maintenance and to incorporate changes. As referenced with other markets in the world, great dynamics is observed in incorporating information and communication technologies, regulatory developments or customer requirements. A technological renovation that preserves the acquired knowledge is required, and that allows easily incorporate the development trends of the market. This article presents the results of the proposed methodology for technological renovation framed in Colciencias CNBT 833559938649 technological research project, in management system for electric power market in Colombia, Phase I.